2020
DOI: 10.1007/s00572-020-00976-6
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the phenylpropanoid pathway affect poplar ability for ectomycorrhizal colonisation and susceptibility to root-knot nematodes

Abstract: Nature. This e-offprint is for personal use only and shall not be self-archived in electronic repositories. If you wish to self-archive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication or later and provided acknowledgement is given to the original source of publication and a link is inserted to the published article … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…(2021a), found that phenylpropanoid and flavonoids were increased during the early stages of EcM colonization, compounds that Behr et al . (2020) were able to positively correlate with EcM colonization. In our results, however, we found these pathways were downregulated during the physical integration stage of colonization in E. grandis before being positively expressed during the functional symbiosis phase.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…(2021a), found that phenylpropanoid and flavonoids were increased during the early stages of EcM colonization, compounds that Behr et al . (2020) were able to positively correlate with EcM colonization. In our results, however, we found these pathways were downregulated during the physical integration stage of colonization in E. grandis before being positively expressed during the functional symbiosis phase.…”
Section: Discussionmentioning
confidence: 90%
“…Similar gene classes have been found to be regulated in EcM interaction with Populus, Pinus, and aspen, although the direction and magnitude of how these pathways are impacted is not consistent (Weiss et al, 1997;Li et al, 2014;Liao et al, 2014;Plett et al, 2015b;Basso et al, 2019). Transcriptomically Weiss et al (1997), and metabolomically Plett et al (2021a), found that phenylpropanoid and flavonoids were increased during the early stages of EcM colonization, compounds that Behr et al (2020) were able to positively correlate with EcM colonization. In our results, however, we found these pathways were downregulated during the physical integration stage of colonization in E. grandis before being positively expressed during the functional symbiosis phase.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Plant contact with ECM fungi has previously been shown to induce phenylpropanoid metabolism, and it has been suggested that the presence of these metabolites aids in limiting over-colonisation by the fungus [ 47 , 48 , 49 ]. However, more recent work involving transgenic down-regulation of genes within the phenylpropanoid pathway suggests that production of these compounds is, in fact, beneficial for mycorrhiza formation, though this could also stem from secondary hormone effects [ 50 ]. Flavonoids are also important attractants of ECM fungi, inducing spore germination, hyphal growth or the production of effector proteins within the fungus [ 16 , 17 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the silencing of cinnamoyl-CoA reductase gene reduced lignin in poplar trees, but also significantly changed the bacterial community in roots, stems, and leaves (Beckers et al, 2016). Similarly, poplar trees downregulated in genes encoding for the lignin biosynthetic enzymes caffeoyl-CoA O-methyltransferase, caffeic acid O-methyltransferase, cinnamoyl-CoA reductase, and cinnamyl alcohol dehydrogenase all displayed a lower mycorrhizal colonization in vitro (Behr et al, 2020). Thus, although growing engineered switchgrass with reduced lignin could have obvious industrial advantages regarding deconstruction and conversion processes, the impact of the engineered trait on the structure and functioning of the plant microbiome needs to be evaluated.…”
Section: Introductionmentioning
confidence: 99%